2020
DOI: 10.1186/s12889-020-8255-2
|View full text |Cite
|
Sign up to set email alerts
|

Current and former smokers among adolescents aged 12–17 years in Iran: a systematic review and meta-analysis

Abstract: Background: Smoking, especially among adolescents, is considered a serious public health concern worldwide being associated with increased mortality. The present study was designed as the first systematic review and metaanalysis of the prevalence of current and former smoking behavior among adolescents in Iran. Methods: Seven international scholarly databases, namely Scopus, Embase, Pubmed/Medline, ISI/Web of Science (WOS), the Cochrane Library, Psyc Info and Cinahl, were extensively searched from January 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…In another study conducted in Iran, the prevalence of smoking among girls aged 12 to 17 years old was found to be 6%. (17). A study conducted in Central and Eastern Europe found that the prevalence of smoking among women was 64.7 %, which was fortunately very high when compared to the ndings of this study (18).…”
Section: Resultscontrasting
confidence: 41%
“…In another study conducted in Iran, the prevalence of smoking among girls aged 12 to 17 years old was found to be 6%. (17). A study conducted in Central and Eastern Europe found that the prevalence of smoking among women was 64.7 %, which was fortunately very high when compared to the ndings of this study (18).…”
Section: Resultscontrasting
confidence: 41%
“…The results of a meta-analysis study in China showed that the prevalence of smoking among women was 5.34% [ 11 ]. The results of a meta-analysis study in Iran showed that the prevalence of smoking among girls aged 12 to 17 years old was 6% [ 12 ]. A study conducted in Central and Eastern Europe showed that the prevalence of smoking among women was 64.7% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a confidence level of 0.95%, a proportion of 0.12, an accuracy of 0.03, and a sample loss of 25%, the sample size was estimated to be 604 subjects [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the World Health Organization (WHO) report, 8.5% of girls have used tobacco, of which 5.5 and 4.8% are currently using tobacco and cigarette respectively [ 3 ]. The results of a meta-analysis study conducted in 2020 showed that the current and ever prevalence of cigarette smoking in Iranian adolescent girls were 6 and 12%, respectively [ 11 ]. The prevalence of cigarette smoking in women increases the risk of cardiovascular disease, stroke, shortness of breath, cervical cancer, and breast cancer [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation